Staphylococcus capitis Bloodstream Isolates: Investigation of Clonal Relationship, Resistance Profile, Virulence and Biofilm Formation - Romero, Letícia Calixto [UNESP]; Silva, Lucas Porangaba [UNESP]; Teixeira, Nathalia Bibiana [UNESP]; de Camargo, Karen Vilegas [UNESP]; Del Masso Pereira, Milena Aparecida [UNESP]; Corrente, José Eduardo [UNESP]; Pereira, Valéria Cataneli; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (MDPI, 2024)
Staphylococcus capitis has been recognized as a relevant opportunistic pathogen, particularly its persistence in neonatal ICUs around the world. Therefore, the aim of this study was to describe the epidemiological profile of clinical isolates of S. capitis and to characterize the factors involved in the persistence and pathogenesis of these strains isolated from blood cultures collected in a hospital in the interior of the state of São Paulo, Brazil. A total of 141 S. capitis strains were submitted to detection of the mecA gene and SCCmec typing by multiplex PCR. Genes involved in biofilm production and genes encoding enterotoxins and hemolysins were detected by conventional PCR. Biofilm formation was evaluated by the polystyrene plate adherence test and phenotypic resistance was investigated by the disk diffusion method. Finally, pulsed-field gel electrophoresis (PFGE) was used to analyze the clonal relationship between isolates. The mecA gene was detected in 99 (70.2%) isolates, with this percentage reaching 100% in the neonatal ICU. SCCmec type III was the most prevalent type, detected in 31 (31.3%) isolates and co-occurrence of SCCmec was also observed. In vitro biofilm formation was detected in 46 (32.6%) isolates but was not correlated with the presence of the ica operon genes. Furthermore, biofilm production in ICU isolates was favored by hyperosmotic conditions, which are common in ICUs because of the frequent parenteral nutrition. Analysis of the clonal relationship between the isolates investigated in the present study confirms a homogeneous profile of S. capitis and the persistence of clones that are prevalent in the neonatal ICU and disseminated across the hospital. This study highlights the adaptation of isolates to specific hospital environments and their high clonality.
Keywords: biofilm; blood culture; clones; coagulase-negative staphylococci; mecA; neonatal ICU; PFGE; SCCmec